Professional quality of life and its associated factors among Vietnamese doctors and nurses - Anh N. P. Tran; Quyen G. To; Van-Anh N. Huynh; Khoi M. Le; Kien G. To (BMC, 2023)
Abstract Background Prevalence of health workers with occupational health issues ranked fourth among all careers resulting in a reduction in quality of life. However, tools to measure professional quality of life (ProQoL) are unavailable in Vietnamese. This study aims to develop a Vietnamese version of the ProQoL, and examine ProQoL and its associated factors among doctors and nurses. Methods The ProQoL is comprised of 30 items measures compassion satisfaction (CS), burnout (BO), and secondary traumatic stress (STS). The tool was translated into Vietnamese following the Guideline by Guillemin et. al (1993), reviewed by expert panels, and validated for internal consistency and test-retest reliability among 38 health workers working at hospitals in HCMC. The validated tool was then used in a cross-sectional study to measure the ProQoL of full-time doctors and nurses working in clinical departments at the University Medical Center, University of Medicine and Pharmacy at Ho Chi Minh City, Vietnam. In addition to the ProQoL, self-reported data about demographic and occupational characteristics were collected. Results The Vietnamese version of ProQoL achieved high internal consistency (alphas between 0.85 and 0.91) and Intra-class Correlation Coefficients (ICCs between 0.71 and 0.89) for all subscales. Among 316 health workers, mean scores of CS, BO, STS were 36.4 (SD = 5.4), 24.9 (SD = 5.1), 25.9 (SD = 5.3), respectively, indicating moderate levels of CS, BO and STS. Participants who were older (b = 0.17, 95%CI = 0.08, 0.26), had sufficient perceived income (b = 2.59, 95%CI = 0.93, 4.24), and > 10 years of working experience (b = 2.15, 95%CI = 0.68, 3.62), had higher CS scores. Those who were older (b=-0.15, 95%CI=-0.23, -0.07), had sufficient perceived income (b=-2.64, 95%CI=-4.18, -1.09), > 10 years of experience (b=-1.38, 95%CI=-2.76, -0.01), worked in surgical department (b=-1.46, 95%CI=-2.54, -0.38) and 8 hours/day (b=-1.52, 95%CI=-2.61, -0.44), had lower BO scores. Moreover, those in a relationship (b=-2.27, 95%CI=-3.53, -1.01) and had sufficient perceived income (b=-1.98, 95%CI=-3.64, -0.32) had lower STS scores. Conclusions The Vietnamese version of ProQoL is valid and reliable for use among Vietnamese health workers. Age, marital status, perceived income status, years of working experience, daily working hours, and specialty was associated with at least one component of ProQoL but gender, religion, education level, and monthly income were not.